Supporting children in public care in schools : a resource for trainers of teachers, carers and social workers - Holland, John, 1948- (JKP resource materials Supporting children in public care in schools, 2005)
Supporting Children in Public Care in Schools is a training package designed for delivery to teachers, social workers, carers and all those supporting young people who are in public care. Based on collaborative multi-agency and multi-professional work with psychologists, teachers and social workers, Supporting Children in Public Care in Schools focuses on the different types of loss that children in care may experience as a result of significant changes in placement, such as the loss of family.